Endoplasmic Reticulum Stress, a Target for Drug Design and Drug Resistance in Parasitosis - Peng, Mei; Chen, Fang; Wu, Zhongdao; Shen, Jia (Frontiers in Microbiology, 2021)
Endoplasmic reticulum stress (ER stress) can be induced when cellular protein homeostasis is damaged, and cells can activate the unfolded protein response (UPR) to restore protein homeostasis or induce cell death to facilitate the survival of the whole system. Globally, parasites are a constant threat to human health and are therefore considered a serious public health problem. Parasitic infection can cause ER stress in host cells, and parasites also possess part or all of the UPR under ER stress conditions. In this review, we aim to clarify the role of ER stress pathways and related molecules in parasites for their survival and development, the pathogenesis of parasitosis in hosts, and the artemisinin resistance of Plasmodium, which provides some potential drug design targets to inhibit survival of parasites, relieve pathological damage of parasitosis, and solve the problem of artemisinin resistance.